ระบบสนับสนุนการจัดตารางการผลิตบนโปรแกรม MFG/PRO - นพดล นิ่มระวี (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The objective of this thesis is to improve the way of work of production planners in developing appropriate production schedules by the MFG/PRO program. This is because the MFG/PRO program which is currently implemented in the sample company does not fully support the development of the production scheduling. Hence there is a need for a supporting program to reduce such problem and support in production planning without any impact on the master program (MFG/PRO). The support program is developed and customized in the program for the sample factory. The scheduling technique applied EDD (Earliest Due Date) that is a heuristic. The support program can run under MFG/PRO program. The result after implementation the supporting program to sample factory is that the sample factory can decrease the time for developing the production scheduling plan and also decrease the preparation time for the production schedule to support the unpredictable events, e.g. machine breakdown. Besides, the actual factory performance is improved continuously.